Popularization of mothbean cultivation in Rajasthan - Meena, M S; Mishra, J P; Meena, H N (Indian Farming, 2024)
India experienced pulses revolution during last 10 years due to the concerted efforts of all stakeholders. One of the innovation in frontline extension approach implemented since 2016-17 was FLDs in clusters in place of individual farmers’ field. The CFLDs were initiated under ICAR-DAFW collaborative project implemented by frontline extension institutions at districts. This proved an effective tool in educating farmers about improved cultivars and agro-techniques of pulses. Over a dozen pulse crops are grown in one or the other part of the country. One of the most climate resilient and stress adaptive pulse crops in India is mothbean, of which over 94% is produced in arid region of Rajasthan. The farmers harvest very low productivity of this crop due to traditional practices and use of farm saved seeds of old varieties. The CFLDs on mothbean were implemented in 6 districts of western Rajasthan for popularization of improved technologies amongst farmers. The demonstrations proved the merits of improved package of practices and varieties with 34.7% yield advantage over farmer’s practices and farm saved seeds of crop varieties. In monetary terms, ₹ 27.8 lakh additional income was generated from CFLD farmers’ fields. The CFLDs have been unique in attracting the farmers and extension personnel for understanding the improved technologies and future requirement to fine tune or modify the technologies for easy adoptability at farmer’s fields. Improvements in this approach with continuous and coordinated efforts shall help in developing and deploying high-yielding and climate resilient varieties as well as practices of moth bean for diversified agri-food systems in the arid regions.